Genetics of multiple sclerosis. - Ebers, G; Dyment, D (1998)
Multiple sclerosis (MS) is a common demyelinating disease of the central nervous system affecting primarily young adults. Evidence from genetic epidemiological studies demonstrate that the observed familial clustering of MS is primarily due to shared genes between family members. Molecular investigations have failed to elucidate susceptibilty loci with the exception of the HLA DRB1*1501, DQA1*0102, DQB1*0602 haplotype of the major histocompatibility complex. Results from genomic screens stress the complexity of MS genetics and that there is no one single locus contributing significantly to familial risk. To overcome the confounding effects of genetic complexity, MS genetic research needs to take advantage of clinical and epidemiological information to better homogenize study samples. In addition, the continued collection and genotyping of MS families may shed some light on the mild to moderate susceptibility loci affecting the MS patient population.